2016
DOI: 10.1039/c5ob02598b
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an ionic liquid on unimolecular substitution processes: the importance of the extent of transition state solvation

Abstract: The reaction of bromodiphenylmethane and 3-chloropyridine, which proceeds concurrently through both unimolecular and bimolecular mechanisms, was examined in mixtures of acetonitrile and an ionic liquid. As predicted, the bimolecular rate constant (k2) gradually increased as the amount of ionic liquid in the reaction mixture increased, as a result of a minor enthalpic cost offset by a more significant entropic benefit. Addition of an ionic liquid had a substantial effect on the unimolecular rate constant (k1) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
5
31
0
Order By: Relevance
“…In contrast to the stabilization of the cyclic ether product caused by the NTf 2 acceptance of the proton, the protonated cyclic ether form in unsupported reaction is energetically very unfavorable in its transformation to the final product by later deprotonation. This behavior has been observed for other reported reactions in ILs, where the IL effect is correlated with the hydrogen bond accepting ability of the IL anion, as well as the transition state IL solvation …”
Section: Resultssupporting
confidence: 80%
“…In contrast to the stabilization of the cyclic ether product caused by the NTf 2 acceptance of the proton, the protonated cyclic ether form in unsupported reaction is energetically very unfavorable in its transformation to the final product by later deprotonation. This behavior has been observed for other reported reactions in ILs, where the IL effect is correlated with the hydrogen bond accepting ability of the IL anion, as well as the transition state IL solvation …”
Section: Resultssupporting
confidence: 80%
“…χ 2 >0.2 is unusual and resembles trends observed for unimolecular substitution processes ,,. These observations could intimate that there are similar interactions occurring in the triphenylantimony 1 d system that are responsible for the observed effects on the rate constant as have been noted in the unimolecular substitution processes (those between the ionic liquid and the transition state), once again this shall be discussed subsequently when further data is presented.…”
Section: Resultssupporting
confidence: 58%
“…The former argument is considered more likely given the charge development in the transition state ( Figure 2) and the potential for either the cation or the anion of the ionic liquid to interact with that charge development. [29] For the reactions studied here these results demonstrate that such transition state-ionic liquid interactions must be taken into account when considering solvent effects in these systems before using ionic liquids to promote the rate of reaction in a synthetic scenario. Significantly, the dominance of these interactions (which have been demonstrated by the difference in effects of the salt in the bromide 2 d and chloride 6 d cases) is novel for an S N 2 process with a neutral nucleophile, though some previous studies have suggested similar interactions result in rate constant enhancement.…”
Section: Effect Of Varying the Leaving Group On The Electrophilementioning
confidence: 68%
“…[21] Rather, such activation parameter changes have been seen before for S N 1 processes where a greater degree of charge development in the transition state would be expected. [29] For the reactions studied here these results demonstrate that such transition state-ionic liquid interactions must be taken into account when considering solvent effects in these systems before using ionic liquids to promote the rate of reaction in a synthetic scenario.…”
Section: Effect Of Varying the Leaving Group On The Electrophilementioning
confidence: 68%